Measuring care: Gender, empowerment, and the care economy - Folbre, Nancy (Journal of Human Development, 2006)
How should “care” be defined and measured in ways that enhance our understanding of the impact of economic development on women? This paper addresses this question, suggesting several possible approaches to the development of indices that would measure gender differences in responsibility for the financial and temporal care of dependents.
Keywords: care; discipline; macroéconomie; projet charge mentale; périodes; sciences de la gestion; soins aux personnes dépendantes; thématiques; travail; travail invisible; économie

Pour une théorie générale de l'exploitation. Deuxième partie: repartir du bon pied - Delphy, Christine (Mouvements, 2004)
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; cours; cycles supérieurs; discipline; discours dominant; exploitation; fem9000; intersectionnalité; marxisme; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; thématiques; travail; violences; économie; économie sociale

L'économie sociale du point de vue des femmes - Corbeil, Christine; Descarries, Francine; Galerand, Elsa (LAREPPS, 2002)
Actes du colloque
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; discipline; division sexuelle du travail; périodes historiques; québec; ressource en ligne; régions géographiques; sciences de la gestion; thématiques; travail; économie; économie sociale